IMPLEMENTATION OF BUSINESS LICENCING POLICIES WITH THE ONLINE SINGLE SUBMISSION SYSTEM IN THE ONE-STOP INTEGRATED SERVICE AND INVESTMENT OFFICE OF THE CITY OF SUKABUMI - Dewianti Dewianti; Rijal Amirulloh; Rizki Hegia Sampurna (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The complicated bureaucratic time makes people not want to register their business, with the online single submission policy it is hoped that it will make it easier for people to get their business licenses. To find out how the Implementation of Business Licensing Policies with the Online Single Submission System at the One-Stop Investment and Integrated Services Office of Sukabumi City. In this study, researchers used descriptive qualitative research methods. Based on the results of research conducted by researchers by collecting data to discuss the implementation of the online single submission system policy at the Sukabumi City One-Stop Investment and Integrated Service Office from Van Metter and Van Horn Theory, there are two variables that are not optimal, namely the resource variable and the Inter-Organizational Coordination and Implementation Activity variable. It can be concluded that human resources in policy implementation are sufficient. However, facilities and infrastructure such as parking lots and expansion of waiting rooms have not been fully realized. then Inter-Organizational Coordination and Implementing Activities have not gone well due to the uneven delivery of information related to the licensing issuance process. However, internal communication is well established.